Makna Keberkahan Rezeki dalam Surah Al Baqarah Ayat 261: Kajian terhadap Konsep Sedekah di Era Ekonomi Digital - Reka Suri; Muhammad Ali Azmi Nasution (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2026)
This study aims to analyze the meaning of the blessing of sustenance in Surah Al-Baqarah verse 261 and its relevance to the practice of charity in the digital economic era. This research employs a qualitative method using library research and a thematic interpretation (maudhu’i) approach. Primary data were obtained from the Qur’an, particularly Surah Al-Baqarah verse 261, as well as classical and contemporary tafsir books, while secondary data were collected from books, journals, and reports related to Islamic economics and digital philanthropy. Data analysis was conducted through documentation study and content analysis. The findings reveal that charity is one of the main means of obtaining blessed sustenance, which is not only oriented toward material multiplication but also encompasses spiritual and social dimensions. In the digital economic era, charitable practices have transformed through digital platforms that facilitate access, increase public participation, and broaden the distribution of assistance. This study concludes that the concept of blessed sustenance in Surah Al-Baqarah verse 261 remains relevant as an ethical and spiritual foundation for digital charity practices amid the development of the modern economy. Keywords: Blessed Sustenance, Digital Charity, Digital Economy, Surah Al-Baqarah Verse 261, Thematic Interpretation,